Paired Remote Ischemic Preconditioning in Recipients and Living Donors Can Mitigate Cardiovascular Stress in Recipients After Living-Donor Kidney Transplantation: A Propensity-Score-Matching Analysis - Jaewon Huh; Min Suk Chae (Medicina)
Background and Objectives: This study explored the effect of paired remote ischemic preconditioning (RIPC), involving both recipients and living donors, on cardiovascular stress in recipients after living-donor kidney transplantation (LDKT). The analysis included an assessment of the impact on cardiovascular biomarkers and post-transplant cardiovascular clinical events. Materials and Methods: A retrospective observational cohort study of 520 adult LDKT patients was conducted, employing propensity score matching (PSM) to analyze perioperative factors. The patients were allocated to no-RIPC (n = 260) and paired-RIPC (n = 260) groups. The two groups were compared with respect to high-sensitivity troponin I (hsTnI) and B-type natriuretic peptide (BNP) levels, corrected QT (QTc) intervals, the occurrence of arrhythmia, and the requirement for cardiovascular interventions. Results: After PSM, there were no significant differences in perioperative parameters between the no-RIPC and paired-RIPC groups. However, on postoperative day (POD) 1, higher hsTnI levels and QTc interval prolongation, as well as higher incidences of arrhythmia and the need for percutaneous coronary intervention (PCI), were determined in the no-RIPC group than in the paired-RIPC group. The associations between paired RIPC and improved cardiovascular outcomes were significant, including reduced odds of elevated hsTnI levels, QTc prolongation, and arrhythmia. The no-RIPC group also had longer intensive care unit (ICU) stays, and higher rates of rescue dialysis. Conclusions: Paired-RIPC involving recipients and donors effectively reduces cardiovascular stress markers and improves postoperative cardiovascular outcomes in LDKT recipients, underscoring its potential as a protective strategy against perioperative cardiovascular risks.